Hydraulic retention time effects on wastewater nutrient removal and bioproduct production via rotating algal biofilm reactor. (July 2016) - Iman Shayan, Sahand; Agblevor, Foster A.; Bertin, Lorenzo; Sims, Ronald C.
Highlights: Rotating algal biofilm reactors were designed for wastewater nutrient removal. Municipal wastewater in secondary stage was fed to the algal–bacterial culture. Hydraulic retention time was main variable factor in fed-batch mode operation. Competitive environment was applied in the bioprocess of mixed culture. Nutrient removal and carbon storage were affected by hydraulic retention time. Abstract: Rotating algal biofilm reactor (RABR) technology was successfully employed in an effective strategy to couple the removal of wastewater nutrients with accumulation of valuable bioproducts by grown algae. A secondary stage municipal wastewater was fed to the developed system and the effects of the hydraulic retention time (HRT) parameter on both nutrient removal and bioproduct production were evaluated under fed-batch operation mode. Two sets of bench scale RABRs were designed and operated with HRTs of 2 and 6 days in order to provide competitive environment for algal growth. The HRT significantly affected nitrogen and phosphorus uptakes along with lipid and starch accumulations by microalgae in harvested biofilms. Domination of nitrogen removal in 2-day HRT with higher lipid accumulation (20% on dried weight basis) and phosphorus removal in 6-day HRT with higher starch production (27% on dried weight basis) was observed by comparing the performances of the RABRs in duplicate runs.